Electronics Engineering Students' Understanding of and Experience with Troubleshooting Skills: A Case Study at a South African University - Jonathan Fatokun; Mishack Thiza Gumbo (Universitas Majalengka, 2026)
Troubleshooting skills is essential in engineering but not often emphasized in Electronics Engineering (EE) education and curricula, which is of significant concern for students entering the industry. While many engineers are trained to design early on, few design new systems in their careers; instead, they often have the need to troubleshoot systems and circuits. This case study qualitative research at a South African university explored the troubleshooting experiences and understanding of the EE students. Through purposive sampling, six undergraduate EE students were identified as participants. The data generated were analysed using a phenomenographic approach. The study showed that EE students practiced troubleshooting throughout their studies but found it challenging and often self-learned. They admitted that troubleshooting is a complex and cognitive process that requires concerted critical thinking efforts to trace faults and analyse problems. Furthermore, since troubleshooting is embedded in the design process, it was always anticipated. Finally, previous industry experience aided EE students’ understanding and proficiency in troubleshooting skills. There is, therefore, a need to connect troubleshooting skills with other engineering competencies in EE student training through curriculum innovation, adaptive pedagogy, and the incorporation of practice-based troubleshooting into engineering education in higher institution standards.